2019
DOI: 10.1364/jocn.11.000465
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and grooming in MPLS over WDM networks

Abstract: AcknowledgementsGostaria de agradecer à Professora Lúcia Martins, por me ter convidado a participar neste projecto e pela sua orientação e apoio ao longo do desenvolvimento da tese.Quero agradecer também ao Dr. João Santos, por estar sempre disponível para esclarecer qualquer dúvida.Agradeço também à CORIANT Portugal, por terem oferecido uma bolsa para a realização deste projecto.Quero também deixar uma palavra de agradecimento à Professora Teresa Gomes, por estar sempre disponível para esclarecimentos.Queria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…It is observed that the priorities of path establishment methods have significant effect over routing performance [15]. In some literature, ''RWA problem with grooming'' is named as ''grooming, routing and wavelength assignment (GRWA) problem'' [16], [17].…”
mentioning
confidence: 99%
“…It is observed that the priorities of path establishment methods have significant effect over routing performance [15]. In some literature, ''RWA problem with grooming'' is named as ''grooming, routing and wavelength assignment (GRWA) problem'' [16], [17].…”
mentioning
confidence: 99%